Acupuncture versus Sham Acupuncture for Chronic Prostatitis/Chronic Pelvic Pain - Lee, Shaun Wen Huey (Am J Med, 2008)
BACKGROUND: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) afflicts 2–10% of adult men. Available therapies offer little or no proven benefit. Because acupuncture represents an attractive “natural” therapy, we compared the efficacy of acupuncture to sham acupuncture for CP/CPPS METHODS: Participants met US National Institutes of Health (NIH) consensus criteria for CP/CPPS, aged ≥ 20 years old, with total score ≥ 15 on the NIH-Chronic Prostatitis Symptom Index (NIH-CPSI) and symptoms for at least 3 of the preceding 6 months were randomized 1:1 to acupuncture or sham acupuncture. Treatment consisted of twice weekly 30-minute sessions for 10 weeks (20 sessions total), without needle stimulation, herbs or adjuvants. The primary response criterion was a six-point decrease from baseline to week 10 in NIH-CPSI total score (range 0–43). RESULTS: Thirty-two (73%) of 44 participants responded in the acupuncture group compared to 21 (47%) of 45 sham group participants (relative risk [RR] 1.81, 95% confidence interval [CI], 1.3–3.1, p=0.02,). Long-term responses 24 weeks after completing therapy without additional treatment occurred in 14 (32%) of 44 acupuncture group participants and in 6 (13%) of 45 sham group participants (RR 2.39, 95% CI, 1.0–5.6, p=0.04). CONCLUSION: After 10 weeks of treatment, acupuncture proved almost twice as likely as sham to improve CP/CPPS symptoms. Participants receiving acupuncture were 2.4 fold more likely to experience long-term benefit than participants receiving sham acupuncture.